The prodigiosin change on the surface of Serratia marcescens detected by flow cytometry. Issue 3 (8th September 2021) - Rong, Guangjian; Zhang, Youhong; Chen, Yan; Chen, Jie; Jiang, Nan; Merchuk, Jose C.
Abstract: The potential of flow cytometry for the study of changes in prodigiosin on the cell surface of Serratia marcescens is of academic and practical interest. This is because S . marcescens can produce prodigiosin, a secondary metabolite, with potential use as a cancer‐cell inhibitor. In this study, three groups of bacterial cultures with different carbon sources were compared, and the effect of the addition of cAMP to the sucrose‐based culture was studied. Both cellular morphology and DNA content were detected by flow cytometry, rendering a broad description of the bacterial behavior. It is the first use of flow cytometry to investigate the dynamics of prodigiosin on the surface of S . marcescens during growth in different media. The fluorescence intensity is related to the DNA content, the forward‐scattered light is related to cell volume, and the side‐scattered light is related to the surface morphology, especially the surface prodigiosin. These may contribute to the potential development of a bacterial metabolic monitoring strategy using both DNA content analysis and bacterial morphology based on flow cytometry technique.